(untitled) (AYUSHDHARA, 2017)
Episiotomy procedure is introduced in obstetrical practice more than 200 years ago but is put in frequent practice in the 20th century. Postnatal complications were more common among women who had episiotomy compared to those who did not have episiotomy; hence postpartum care of episiotomy wound should begin as soon as possible. So the present study has been done on episiotomy wound healing. Basically two things Shodhana (cleaning) and Ropana (healing) are desirable for proper healing. Many single drugs and compound formulations have been described in the classics for wound healing. The present study is taken up with the aim of comparison of clinical evaluation of wound healing property of Nimbadi and Yastyadi ointment, topical application on episiotomy wound. Study carried out on total 30 patients, under group A 15 patients treated with Nimbadi ointment, and 15 patients in group B treated with Yastyadi ointment. Both Groups were given local application of ointment on episiotomy wound as per requirement twice a day for a period of 14 days. On observation Group A therapy shows 66.62 % relief in signs and symptoms of wound along with good status of healing (cured) i.e. 53.33%. Group B therapy shows 49.50% relief in signs and symptoms of wound along with average status of healing (Partially cured) i.e. 46.66%. Better result was observed in group A in comparison to group B. No adverse effect was observed in any patient during the trial.